Phenolic acids and their carboxylate anions: Thermodynamics of primary antioxidant action. (August 2022) - Biela, Monika; Kleinová, Andrea; Klein, Erik
Abstract: Phenolic acids represent naturally occurring antioxidants and play important role in free radicals scavenging. In this work, we have studied thermodynamics of the first step of primary antioxidant action for phenolic OH groups of benzoic and cinnamic acid derivatives, and their carboxylate anions. M06–2X/6–311++G(d, p) reaction enthalpies related to Hydrogen Atom Transfer (HAT), Single Electron Transfer – Proton Transfer (SET-PT), and Sequential Proton-Loss Electron-Transfer (SPLET) mechanisms were computed for model non-polar environment (benzene) and aqueous solution. The effect of acid structure on found reaction enthalpies was investigated, as well. For HAT, representing relevant reaction path in both environments, the lowest O–H bond dissociation enthalpies, BDE, were found for sinapic acid (347 kJ mol −1 in benzene and 337 kJ mol −1 in water). With two exceptions, carboxylate anions show lower BDEs than parent acids. In aqueous solution, enthalpies of the first step of SPLET from phenolic OH groups are low (135–199 kJ mol −1 ). It indicates thermodynamic feasibility of the mechanism for acids, as well as their carboxylate anions. Although enthalpies of electron transfer from dianions formed after successive deprotonations of carboxyl and phenolic groups in water are usually higher than BDEs, differences are within 25 kJ mol −1 . Demethylation of OCH3 groups may affect radical scavenging activity of studied substances due to O–CH3 BDE considerably lower (230–269 kJ mol −1 ) in comparison to O–H ones. Graphical abstract: Image 1 Highlights: First step of primary antioxidant effect of phenolic acids is investigated. Effect of structure on enthalpies of H-atom, electron, and H + transfer is studied. Impact of carboxylate group deprotonation in aqueous solution is assessed. Thermodynamically favored process in non-polar and polar environment is identified. Dissociation of methoxy groups may affect radical scavenging activity.